TACIT CONSENT AND COSTS OF NON-ENTRY INTO THE POLITICAL COMMUNITY - Savanović, Aleksandar (Politeia, 2020)
This paper offers an analysis of an issue related to the social contract theory The issue concerned is disagreement in the form of tacit consent. Namely, if we accept the model of tacit consent, then an issue of costs of this disagreement is raised. These costs cannot be treated in the same way as in the case of express consent. The reason is that, in the case of tacit consent, a person does not have same chances and opportunities as others. This offers a possibility of claiming discrimination, especially if we accept the fact that these costs can be so high so that they deny the possibility of choice. At least in a practical sense and de facto. So, this topic must be understood properly if we want  the social contract theory to function well. In this paper, we will try to do that through a logical and semantic analysis of basic terms: tacit consent, disagreement, and costs of contract.
Keywords: tacit consent, express consent, disagreement